2017
DOI: 10.4172/2375-4494.1000343
|View full text |Cite
|
Sign up to set email alerts
|

Drawing-Out Resilience in Children and High-Risk Adolescents via Exposing Them to Three Psycho-Spiritual Principles

Abstract: This preliminary study examines the effects on the resilience and behavior of children and high-risk adolescents via exposing them to three psycho-spiritual principles-Universal Mind, consciousness, and thought. Forty-five children and twenty-six high-risk adolescents were randomly assigned to experimental groups. Treatment participants received ten 60-90 minute lessons designed to help them understand how the principles of Universal Mind, consciousness, and thought interact from within to construct their psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Kelley, Pransky, and Lambert (2016b) reported that participants exposed to the three principles reported significant improvements in TR and IH/CM, and in turn significant improvements in mindful attention, mindful acceptance, flow experience, and mental wellbeing. Finally, Kelley, Alexander, and Pransky (2017) reported that compared to a waitlist control group, children and adolescents exposed to the three principles showed a significant increase in resilience. Also, "high-risk" participants reported a significantly greater improvement in overall resilience than moderate and low-risk participants, as well as a significant decrease in risky behavior.…”
Section: Supportive Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Kelley, Pransky, and Lambert (2016b) reported that participants exposed to the three principles reported significant improvements in TR and IH/CM, and in turn significant improvements in mindful attention, mindful acceptance, flow experience, and mental wellbeing. Finally, Kelley, Alexander, and Pransky (2017) reported that compared to a waitlist control group, children and adolescents exposed to the three principles showed a significant increase in resilience. Also, "high-risk" participants reported a significantly greater improvement in overall resilience than moderate and low-risk participants, as well as a significant decrease in risky behavior.…”
Section: Supportive Empirical Evidencementioning
confidence: 99%
“…The authors have provided detailed explanations of the three principles elsewhere (for a review, see Kelley, Pransky, & Lambert, 2014, 2015a, 2016a, 2016bKelley, Alexander & Pransky, 2017). Here, we review the three principles and explain how they appear to combine to form people's psychological lives.…”
mentioning
confidence: 97%
“…The total 3PI score ranges from 11 to 55 with higher scores indicating greater knowledge of program content. The 3PI has demonstrated adequate reliability (Cronbach's alpha = 0.70) when used with adults (Kelley et al, 2017a(Kelley et al, , 2017b. Reliability analysis indicated a Cronbach's alpha of 0.73 for the 3PI in our study sample (using both pre-and post-data).…”
Section: Level Of Knowledge Of Program Contentmentioning
confidence: 57%
“…By increasing understanding and insights around these principles, children can access and experience their natural, innate well-being and prevent negative developmental outcomes (Kelley, 2003). Uncovering and strengthening these competencies within children can reinforce their resilience and bolster their capacity to manage the relationships, responsibilities, expectations, and challenges they face (Kelley et al, 2017a(Kelley et al, , 2017b. As suggested by Banerjee et al (2007), targeting the principles of Mind, Thought, and Consciousness is likely to produce more sustainable change than simply targeting an individual's thoughts, thought processes, feelings, and behaviors.…”
Section: Spark Child Mentoring Programmentioning
confidence: 99%
“…Another article that presented the existing correlations between resilience, abnormal behavior in children and adolescents was published by Kelley et al [3]. The authors explored the role of exposing the children to the three most widely known psycho-spiritual principles viz.…”
mentioning
confidence: 99%